Endoscopic ultrasound-guided hepaticogastrostomy versus percutaneous transhepatic drainage for malignant biliary obstruction after failed endoscopic retrograde cholangiopancreatography: a retrospective expertise-based study from two centers - Sportes, Adrien; Camus, Marine; Greget, Michel; Leblanc, Sarah; Coriat, Romain; Hochberger, Jürgen; Chaussade, Stanislas; Grabar, Sophie; Prat, Frédéric (Therapeutic advances in gastroenterology, 2017)
Background: Percutaneous transhepatic biliary drainage (PTBD) is widely performed as a salvage procedure in patients with unresectable malignant obstruction of the common bile duct (CBD) after failed endoscopic retrograde cholangiopancreatography (ERCP) or in case of surgically altered anatomy. Endoscopic ultrasound-guided hepaticogastrostomy (EU-HGS) is a more recently introduced alternative to relieve malignant obstructive jaundice. The aim of this prospective observational study was to compare the outcome, efficacy and adverse events of EU-HGS and PTBD. Methods: From April 2012 to August 2015, consecutive patients with malignant CBD obstruction who underwent EU-HGS or PTBD in two tertiary-care referral centers were included. The primary endpoint was the clinical success rate. Secondary endpoints were technical success, overall survival, procedure-related adverse events, incidence of adverse events, and reintervention rate. Results: A total of 51 patients (EU-HGS, n = 31; PTBD, n = 20) were included. Median survival was 71 days (range 25–75th percentile; 30–95) for the EU-HGS group and 78 days (range 25–75th percentile; 42–108) for the PTBD group (p = 0.99). Technical success was achieved in all patients in both groups. Clinical success was achieved in 25 (86%) of 31 patients in the EU-HGS group and in 15 (83%) of 20 patients in the PTBD group (p = 0.88). There was no difference in adverse events rates between the two groups (EU-HGS: 16%; PTBD: 10%) (p = 0.69). Four deaths within 1 month (two hemorrhagic and two septic) were considered procedure related (two in the EU-HGS group and two in the PTBD group). Overall reintervention rate was significantly lower after EU-HGS (n = 2) than after PTBD (n = 21) (p = 0.0001). Length of hospital stay was shorter after EU-HGS (8 days versus 15 days; p = 0.002). Conclusions: EU-HGS can be an effective and safe mini invasive-procedure alternative to PTBD, with similar success and adverse-event rates, but with lower rates of reintervention and length of hospitalization.